Introduction to investor-state arbitration - Derains, Yves (Kluwer Law International B.V., 2018)
Introduction to Investor-State Arbitration' focuses on sometimes difficult concepts of investor-State arbitration in a clear and concise explanatory manner while drawing attention to important cases. Today thousands of investors act globally in markets providing services, technology or capital in countries all around the world. This activity can be peacefully accomplished when both the investor and the host State know that the disputes will be resolved under the aegis of the investor-State arbitration regime, wherein an investor is provided with a direct right of action against a State, most commonly stemming from a bilateral investment treaty or a multilateral treaty such as the Energy Charter Treaty and the North American Free Trade Agreement, as well as public contracts.